Different perspectives associated with the development of relevant strategies for maintenance of withdrawal period of veterinary drugs: Bangladesh perspectives (Asian-Australasian Journal of Food Safety and Security, 2018)
Veterinary drugs have proven to be one of the most valuable tools in preserving animal health. With an increase in the use and availability of veterinary drugs, residues of veterinary drugs in animal origin food has become a public health concern and has received much attention from government agencies, consumer level, media and other concerned public interest groups. The objectives of the study were to identify the perspectives associated with the poor management for maintenance of withdrawal period of veterinary drugs in Bangladesh so that the development of relevant strategies for maintenance of withdrawal period of veterinary drugs could be achieved in context of environmental realities in Bangladesh. The survey was interpretive in nature using quantitative methods. A non-experimental and descriptive research design was used to conduct this study. The survey study was carried out at seven divisions (i.e. Rangpur, Rajshahi, Khulna, Dhaka, Sylhet, Barishal and Chattogram) in Bangladesh during July 2012 to June 2018 by using close ended questionnaires among randomly selected respondents. Survey instruments were also designed to capture the perspectives of two different groups of government veterinarians: Group 1– Veterinary Surgeons of DLS, Bangladesh and Group 2 –Upazila Livestock Officers of DLS, Bangladesh. The findings indicated the knowledge, beliefs and perceptions of respondents. The research findings divulge that different perspectives/dimensions associated with economic loss, compensation support, awareness, ethical motivation, monitoring system, proper legislation and guideline, cooperative and group livestock production as well as marketing system had „moderate to substantial role‟ with the management for maintenance of withdrawal period of veterinary drugs in Bangladesh. Besides these, findings also indicated that other perspectives/dimensions associated with allocation of subsidies and Bank loan with low interest, opportunity of livestock/ poultry insurance services, capacity enhancement for monitoring system, availability of technology to producers level, extension work with motivation, magistracy empowerment for veterinarians, legal influence, capacity enhancement of DLS staff, building of public awareness on drug residue problem and availability of effective equipment as well as modern analytical techniques for diagnostic analysis of chemical/drug residues also had „moderate to substantial role‟ with the development of relevant strategies for maintenance of withdrawal period of veterinary drugs. Findings indicated that the two groups of veterinarians possessed near to similar/same perceptions across different dimensions/perspectives associated with the development of relevant strategies for maintenance of withdrawal period of veterinary drugs in Bangladesh and that no significant differences in perspectives existed (p> .05). Findings of this study could be implemented for formulation of effective policy as well as guideline with the development of relevant strategies for maintenance of withdrawal period of veterinary drugs in context of environmental realities in Bangladesh.Asian Australas. J. Food Saf. Secur. 2018, 2(2), 71-78